Pengaruh Kualitas Produk Persepsi Harga Dan Kestrategisan Lokasi Terhadap Keputusan Pembelian Pada Toko Busana Muslim MCP - Diah Ayu Sekarnadi; Handy Aribowo; Anis Fitriyasari; Iswati Iswati; Ageng Pratiwi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The purpose of this study was to find out and analyze how much influence Product, Price and Strategic Location have on Purchasing Decisions at the MCP Royal Plaza Surabaya Muslim fashion store. This study used a quantitative method with a descriptive type with a random sampling technique and the number of respondents was 52 people. The data analysis method used in this study is multiple linear regression analysis, while the results of this study are that price has a significant and significant effect on purchasing decisions as seen from the t count > t table (4.426 > 1.661), and a significant level lower than 0, 05 which is 0.000, it can be seen from the value of t count <t table (-0.064 <1.661) then it can be seen that the significant value is lower than 0.05 which is 0.000 , Service Quality has a significant and significant effect on purchasing decisions seen from t count> t table (2.625 > 1.661) and a lower significant level than 0.05, namely 0.000, Price and Service Quality have a significant and significant effect on the decision to purchase MCP Store products, as seen from the t count > t table f count > f table (19,548 > 2,699) and the value sig 0.000 <0.05 the percentage value that influences the independent variables (Product, Price, Strategic Location) to the dependent variable (Purchase Decision) is 38%. Thus the variable price, strategic location and product quality affect the consumer purchasing decisions of the MCP Muslim fashion store at Royal Plaza Surabaya.